The effects of performances in canoe, kayak and rowing on muscle oxygen saturation: Experimental study - PELVAN, SERDAR ORKUN; AKBAŞ, SAVAŞ (My University, 2023)
Objective: The aim of this study is to compare the intramuscular oxygen saturation results during the short and long distance performances of canoe, kayak and rowing athletes. Material and Methods: 30 male international level and licenced athletes (8 canoeists, 11 kayakers and 11 rowers) are participate to this study; age 20.53±3.23 year, height 181.70±7.90 cm, body weight 78.60±11.22 kg and body mass index 23.73±2.37. The intramuscular oxygen saturation status of athletes were measured using the near infrared spectroscopy technology for 40 second sprint and 4 minutes tests performed on the land with branch-specific ergometers. Data collecting processes were recorded as 5 minute rest, 40 second sprint, 10 minute rest, 4 minute distance performances and 5 minute recovery, in total nearly 25 minute. Results: Comparing the intramuscular oxygen saturation values of canoe, kayak and rowing athletes, no significant difference was found in the decrement rate to minimum, during 40 second sprint for biceps brachii and vastus lateralis (p>0.05). As we compare to 4 minute performances, a significant difference was found in both muscle groups for all three branches. It was seen that the difference was between rowing and canoe athletes, and lower intramuscular oxygen saturation values were found in canoeists compared to rowers (p<0.05). Conclusion: The results show that intramuscular oxygen saturation it can be said that many factors effect such as differences between branches, posture position, cardiovascular differences between athletes, using of body parts, and number of stroke per minute.

Amaç: Bu çalışmanın amacı, kano, kayak ve kürek sporcularının kısa ve uzun mesafe performansları sırasında kas içi oksijen saturasyon sonuçlarını karşılaştırmaktır. Gereç ve Yöntemler: Bu çalışmaya 30 erkek uluslararası düzeyde ve lisanslı sporcu (8 kanocu, 11 kayakçı, 11 kürekçi) katılmıştır; yaş 20,53±3,23 yıl, boy 181,70±7,90 cm, vücut ağırlığı 78,60±11,22 kg ve beden kitle indeksi 23,73±2,37’dir. Sporcuların kas içi oksijen saturasyon durumu, yakın kızılötesi spektroskopi teknolojisi kullanılarak, branşa özel ergometreler ile karada 40 sn sürat ve 4 dk mesafe testleri yapılmıştır. Veri toplama işlemleri 5 dk dinlenme, 40 sn sprint, 10 dk dinlenme, 4 dk mesafe performansları ve 5 dk toparlanma olmak üzere toplamda yaklaşık 25 dk olarak kayıt altına alınmıştır. Bulgular: Kano, kayak ve kürek sporcularının biceps brachii ve vastus lateralis kasları kas içi oksijen saturasyon değerleri karşılaştırıldığında, 40 sn’lik sprintte minimuma düşme hızında anlamlı bir fark bulunmamıştır (p>0,05). Dört dk’lık performansları karşılaştırdığımızda, her üç dal için her iki kas grubunda da anlamlı bir fark bulunmuştur. Farklılığın kürek ve kano sporcuları arasında olduğu görülmüş, kanocularda kürekçilere göre daha düşük kas içi oksijen saturasyon değerleri bulunmuştur (p<0,05). Sonuç: Araştırmamızdaki kas içi oksijen saturasyonunun branşlar arasındaki farklılıklarında, duruş pozisyonunu, sporcular arasındaki kardiyovasküler farklılıkların, vücut bölümlerinin kullanımının, dakikadaki kürek sayısı gibi birçok faktörün etkili olduğu söylenebilir.
Kano, kayak ve kürek performanslarının kas oksijen doygunluğuna etkisi: Deneysel çalışma
Keywords: Near infrared spectroscopy; muscle oxygen saturation; dynamic exercise; oxygenation; Yakın kızılötesi spektroskopisi; kas oksijen doygunluğu; dinamik egzersiz; oksijenasyon